YOUNG PEOPLE’S PERSPECTIVES ON THE SOCIAL EFFECT OF LIFELONG LEARNING POLICIES IN EUROPE - Kovacheva, Siyka; Milenkova, Valentina (Revista Inclusiones, 2020)
The paper examines the perspectives of young people who were participants in lifelong learning programs evaluated by regional experts as being the most effective in two regions in each of nine European countries that were members of the consortium of an international comparative project. The analysis is informed by the theoretical framework of life course research. The evidence base of the paper comes predominantly from the 164 in-depth interviews with young people conducted in 2017 while also taking into consideration the policy analysis of 53 programs and initiative of public and private agencies and 121 semi-structured interviews with regional policy makers and street level professionals. It presents the policy effect as seen by the young themselves: the skills and other results they have achieved while facing a growing insecurity of youth transitions. In this article we have argued that young people in different localities in Europe were commonly willing to take the challenge of further studies and training for their successful integration in the labour market. They evaluated their experiences from the schemes/programs positively and considered that they had developed new skills and abilities that would be useful in the future phases of their life course. The analysis also showed that there were some mismatches from young adults’ perspectives.